Measuring Visual Homogeneity and Congruence in Breast Cancer Awareness Campaigns - Germain Mesureur (COMMUSTY Journal of Communication Studies and Society, 2026)
Breast cancer awareness advertising is globally defined by the colour pink and the iconic pink ribbon. While this branding has elevated the cause, it has also sparked criticism regarding "pinkwashing," where companies exploit it for commercial gain. This study investigates whether these distinctions manifest in the visual design of advertisements. A quantitative content analysis was conducted on 326 static advertisements from 52 countries (2010–2024), measuring dominant colours and coding each advertisement for advertiser type, brand-cause congruence, and pink ribbon usage. Results reveal that neither advertiser type nor brand-cause fit significantly predicts colour choice   commercial campaigns are visually indistinguishable from non-profit messages. Instead, the visual landscape is driven almost entirely by the pink ribbon's presence. Symbolic norms have achieved a hegemony that overpowers individual brand strategies, producing a constrained visual language.